Dynamic electron correlations with charge order wavelength along all directions in the copper oxide plane - F. Boschini (Nature Portfolio, 2021)
Knowledge of effective Coulomb interactions is central to understand emergent quantum phases in strongly correlated systems. Here, Boschini et al. report a dynamic quasi-circular spectrum of charge density wave fluctuations in the CuO2 plane of Bi2Sr2CaCu2O8+δ , shedding a light on understanding how Coulomb interactions can lead to rotational and translational symmetry breaking in the cuprates.